2020
DOI: 10.1111/nmo.14065
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Crataegus azarolus L. berries aqueous extract against castor oil–induced diarrhea, oxidative stress, and inflammation in rat

Abstract: Background: Diarrhea is a multifactorial gastrointestinal disorder responsible for about 5 million deaths annually. The chemical composition, the antioxidant activity of Crataegus azarolus berries aqueous extract (CABAE) as well as its protective effects against castor oil-induced diarrhea, oxidative stress, and inflammation in rat were studied.Methods: Sixty male rats were used and divided into six groups of ten animals in each: Control (C), castor oil (CO), CO+various doses of CABAE (100, 200, and 400 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…In fact, we previously showed that the Crataegus azarolus berries aqueous extract obtained by maceration contained a lower level of total phenolic contents than the decoction extract for the same plant part. 40 Our results are in line with the findings of Castro-López et al 41 In addition, the LC-ESI-MS analysis resulted in the identification of 8 phenolic compounds, among which chlorogenic acid was the major component. In this respect, previous reports demonstrated that this fruit has a very diverse phenolic profile.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, we previously showed that the Crataegus azarolus berries aqueous extract obtained by maceration contained a lower level of total phenolic contents than the decoction extract for the same plant part. 40 Our results are in line with the findings of Castro-López et al 41 In addition, the LC-ESI-MS analysis resulted in the identification of 8 phenolic compounds, among which chlorogenic acid was the major component. In this respect, previous reports demonstrated that this fruit has a very diverse phenolic profile.…”
Section: Discussionsupporting
confidence: 91%
“…Among the several mechanisms to explain the laxative effect of castor oil, one is the inhibition of intestinal Na+/K + -ATPase activity. Thus, reducing normal fluid absorption through activation of adenylate cyclase or mucosal cyclic adenosine monophosphate-mediated active secretion and nitric oxide release [ 23 , 24 ]. Moreover, castor oil promotes smooth muscle contraction via its metabolite, ricinoleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition produced by the standard drug, loperamide, was more than that produced by the extract. Castor oil-induced diarrhea have been shown in previous studies to be inhibited by many plant extracts such as Crataegus azarolus, [35] Bixa orellana, [36] Vitex doniana, [37] and Entada africana. [38] In an attempt to suggest other possible mechanism of activity of the plant extract, the PE 2 enteropooling test was carried out.…”
Section: Discussionmentioning
confidence: 99%